What's in the black box? Evaluating anti-poverty tourism interventions utilizing theory of change. Issue 17 (22nd November 2018) - Phi, Giang Thi; Whitford, Michelle; Reid, Sacha
Abstract : Increasing interest in poverty alleviation at the beginning of twenty-first century has facilitated the rapid growth of various anti-poverty tourism interventions (ATIs) around the globe. The tourism–poverty alleviation link, however, is still not well established, partly due to a paucity of appropriate evaluation approaches that are capable of simultaneously providing researchers, practitioners and policy-makers with a deeper understanding of an ATI's mechanisms, the complexity surrounding its operational processes and evidence of its impacts. Additionally, ATI stakeholders' values and influences play a significant role in ATI evaluation yet their perspectives are often overlooked. Theory of Change (ToC) has the potential to generate a holistic picture of an ATI, as this innovative approach has been developed to connect stakeholders' theories of context with the mechanisms and outcomes of an intervention. Utilizing a case study of microfinance tourism in Vietnam, this paper provides readers with insight into ToC and proposes a conceptual framework which guides the application of ToC to facilitate the effective evaluation of ATIs.